COLLABORATIVE GOVERNANCE DALAM PENANGANAN KASUS KEKERASAN TERHADAP ANAK DIBAWAH UMUR DI KOTA PEKANBARU TAHUN 2017-2019 - Oktafien, Fania; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The violence against children often occurs in children under the age of 0 to 18 years old. Pekanbaru City is one of the cities in Riau Province where the number of violence against children is quite high. The cases of violence against children in Pekanbaru city from 2017 to 2019 according to data from the Woman and Children Protection Service Unit (PPA) have always increased. The cases of violence are divided to: child custody, sexual abuse, domestic violence, children conflict with the law,and neglect of children's rights. Due to the high level of violence against minors, collaboration is needed by stakeholders in handling the cases of violence.The purpose of this research is to find out how collaborative governance in handling the cases of violence against minors in Pekanbaru City in 2017-2019. The theory used in this research is the collaborative model of Ansell and Gash (2007:550). The data Collection techniques used in this research are interviews, observations, and documentation studies. The result of this research indicates that the collaborative governance in handling the cases of violence against minors in Pekanbaru City in 2017-2019 based on initial conditions indicator was not optimal, due to the limited human resources owned by each stakeholder. Next, on the facilitative leadership indicator, the implementation was not optimal due to the absence of a special team that's used as a guide in providing treatment for the minors. On institutional design indicators, the implementation was not optimal due to the absence of standard operating work (SOP) or special rules to regulated violence against minors. Meanwhile, in the collaborative process indicator, the implementation was not optimal because the stakeholders have never had a face-to-face dialogue. Keywords: The violence against children, stakeholder, collaborative governance